KEEFEKTIFAN METODE SIMULASI TERHADAP KETERAMPILAN SOSIALMAHASISWA PADA MATA KULIAH METODOLOGI PEMBE¬LAJARAN DI PGSD UPY - Rina Dyah Rahmawati (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
The purpose of this study was to determine the difference score students’ social skills (social responsibility, cooperation, and tolerance) among students who attend the lecture course learning methods and simulation methods that the lecture method.This research is a quasi experimentation with pretest-posttest control group design. The study population was all students of class 2012 PGSD UPY. Sampel selected by random sampling technique to determine the experimental class. Data obtained by questionnaire with Likert scale and observation sheet to collect data about students’ social skills. Data were analyzed using statistical techniques Analysis Of Variance (ANOVA) and a significance test with α = 0.05. From this study showed that there are significant differences on social skills among students who attend lectures with simulation methods and the students who attend the lecture by lecture method. Social skills (social responsibility, cooperation, and tolerance) students of the experimental class (class using simulation method) higher than the social skills of students in the control class (classes using lecture method) because the simulation method is more interactive, centered on the student, cooperative and creative. Class teaching methodology using simulation method is more effective in improving students’ social skills (social responsibility, cooperation, tolerance) compared with the lecture method.